Marine algae extracts processes, products, and applications - Kim, Se-Kwon; Bazynska-Chojnacka, Katarzyna (Wiley-VCH Verlag GmbH & Co. KGaA, 2015)
Designed as the primary reference for the biotechnological use of macroalgae, this comprehensive handbook covers the entire value chain from the cultivation of algal biomass to harvesting andprocessing it, to product extraction and formulation. In addition to covering a wide range of product classes, from polysaccharides to terpenes and from enyzmes to biofuels, it systematically discusses current and future applications of algae-derived products in pharmacology, medicine, cosmetics, food and agriculture